PLANT-BASED MRNA DELIVERY ADJUVANTS: AN OVERVIEW - Dr. Onkar Bharat Doke; Dr. Samrat Ashok Khedkar; Sakshi Vikas Bhuite; Pravin Laxman Bhong; Shivanjali Dilip Bhagat; Pratibha Jaykumar Bhardwaj (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2025)
Messenger RNA (mRNA) vaccines are a new and powerful type of vaccine that can be quickly designed to protect against infectious diseases and cancer. Even though they are very effective, mRNA vaccines face some challenges, such as instability of mRNA, difficulty in delivering it into cells, and controlling the immune response. To solve these problems, scientists are exploring natural solutions, especially from plants. Plants produce many bioactive compounds such as saponins, polysaccharides, flavonoids, and natural nanoparticles that can help improve mRNA delivery and strengthen immune responses. These plant-derived substances can act as adjuvants, which boost the immune response, or as delivery carriers, which protect mRNA and help it enter cells. Plant-based systems are attractive because they are generally safe, biodegradable, cost-effective, and environmentally friendly. In mRNA vaccines, immune activation can occur in three main ways: through the mRNA itself, through the delivery system such as lipid nanoparticles, and through added immune-stimulating substances. Plant-derived adjuvants can support all these mechanisms by activating immune cells and improving antigen presentation. New plant-based approaches, including plant virus nanoparticles and plant-derived extracellular vesicles, are being studied as alternatives to synthetic delivery systems. Overall, plant-based adjuvants and delivery platforms offer a promising strategy to make mRNA vaccines safer, more stable, and more affordable. With further research and standardization, these natural systems may play an important role in the future development of vaccines and mRNA-based therapies.